Redescription of the poorly known genus Ikuma Lawrence, with synonymy and description of a new species from Namibia (Araneae, Palpimanidae) - Zonstein Sergei; Marusik Yuri M (COUNCIL NATAL MUSEUM, 2022)
The spider genus Ikuma Lawrence, 1938, endemic to Namibia, is rediagnosed and redescribed based on the characters both species originally included in the genus and of the newly described I. larseni sp. nov. A new synonymy is proposed: I. squamata Lawrence, 1938, described from a sole female is recognized a junior synonym of the type species I. spiculosa (Lawrence, 1927), based on a single juvenile. The currently described I. larseni sp. nov. differs from the generotype in the eye arrangement, structure of the abdominal scuta, and details of the colouration. The copulatory organs of both males and females belonging to Ikuma are studied, described and depicted for the first time. The previously known genus range confined to the far north of Namibia extends to the mid-western part of this country.